ANALISIS HOMOGENITAS KEMAMPUAN BERPIKIR DAN PERILAKU SISWA (STUDI KASUS PADA PELAJARAN AGAMA ISLAM) - Candra Wijaya; Muhammad Syafi’i; Tongat Tongat (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The cognitive ability and the student attitude on the Islamic religious course still low. This study aims to reveal a homogeneity analysis of cognitive abilities towards student attitudes that is the limited level. The proof was done with quantitative approach. The data processing was done manually with mathematical equations. The research location at Senior High School Imelda Medan. The total of 21 student was sampled drawn from the XI-Class. The activities were established from july to september 2019. The Likert scale has been suggested instruments to measure student cognitive ability toward influenced of the attituted. The results shows, all the attribute variables had a homogeneous. This means that the data obtained from respondents have a similarity in size distribution so it is feasible for the next stage of analysis.